2021
DOI: 10.1016/j.ajo.2021.03.033
|View full text |Cite
|
Sign up to set email alerts
|

A Smart Mobile Application to Monitor Visual Function in Diabetic Retinopathy and Age-Related Macular Degeneration: The CLEAR Study

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 15 publications
1
16
0
1
Order By: Relevance
“…Our finding that HM was acceptable to patients and could be used to assess the stability of nAMD and monitor associated changes in vision is in keeping with other related research about the monitoring of visual function using digital testing [ 48 , 49 , 50 , 51 ]. For example, a pilot study of a tablet-based programme for detecting progression in patients with intermediate AMD indicated good agreement between HM and clinic-based testing [ 49 ].…”
Section: Discussionsupporting
confidence: 88%
“…Our finding that HM was acceptable to patients and could be used to assess the stability of nAMD and monitor associated changes in vision is in keeping with other related research about the monitoring of visual function using digital testing [ 48 , 49 , 50 , 51 ]. For example, a pilot study of a tablet-based programme for detecting progression in patients with intermediate AMD indicated good agreement between HM and clinic-based testing [ 49 ].…”
Section: Discussionsupporting
confidence: 88%
“…92 Home OCTs and smart phone apps measuring vision, contrast sensitivity, ocular alignment, subretinal fluid, and metamorphopsia may be used for at-home monitoring and earlier detection of disease. [93][94][95] Fundus photographs, slit lamp photography, laser flare photometry, fluorescein angiography, OCTs, and OCTAs can be obtained with minimally trained staff, be remotely operated, or be self-operated. 93,96 Artificial intelligence (AI) or a remote screener can help evaluate the images.…”
Section: Teleophthalmologymentioning
confidence: 99%
“…ing has been done exclusively in a clinical setting under the guidance of a trained professional, but in recent years, various options have been created for testing outside of the clinic, including paper charts, [7][8][9][10] web-based tests, [11][12][13][14] and smartphone applications. [15][16][17][18][19][20][21][22][23][24] Many commercially available VA tests are not validated before public release, and many applications require users to pay a fee, making clinical application unrealistic for some patients. 25 A 2015 review of 11 Snellen chart iPhone applications found significant variability in application accuracy and validation methods.…”
mentioning
confidence: 99%